Analisis Fourth-Generation War Dalam Perang Insurgensi: Studi Kasus Pemberontakan Tentara Pembebasan Nasional Zapatista (Ezln) Di Meksiko - Gunawan Lestari Elake (GLOBAL INSIGHT JOURNAL, 2019)
Like the story of asymmetric fight between David and Goliath, Insurgency war is also the story of an asymmetrical warfare in which highly advanced military parties (usually the State Governments) are often struggling and even failing against small group of insurgents. By taking the case of the Zapatista National Liberation Army (EZLN) uprising, this paper aims to analyze why this armed rebel with poorly military equipments is able to relatively succeded in striving for its political agenda. In doing so, this paper used the concept of Fourth Generation War that emphasizes the importance of using all available networks to attacks the minds of enemy decision makers to destroy their political will. The author show that the main factor that determined EZLN’s trump is its ability to use three important networks, namely; a) Indian communities, b) national and international civil society and, c) internet and independent media networks as means in disseminating their grievances and alternatives. Keywords: insurgency, asymmetry warfare, fourth generation war, EZLN, networks